Metode didactice – mijloc de realizare a continuității și interacțiunii între cicluri de învățământ superior [Articol] - Guțu, Vladimir (CEP USM, 2019)
În acest articol este abordată, pentru prima dată, problema privind metodele didactice ca mijloc de realizarre a continuității și interconexiunii între cicluri de învățământ superior. Accentul se pune pe stabilirea valențelor și oportuunităților metodelor și pe valorificarea principiului continuității și interconexiunii în educație, precum și pe particularitățile aplicării acestora în procesul de predare-învățare-evaluare la diferite cicluri de învățământ superior.

In the given article the problem of teaching methods from the perspective of continuity and interconnection between cycles of higher education is placed addressed for the first time. The emphasis is on establishing the valences and opportunities of the methods and capitalizing on the principle of continuity and interconnection in education, as well as on the peculiarities of their application in the process of teaching-learning-evaluation in different cycles of higher education.
TEACHING METHODS  MEANS OF ACHIEVEMENT OF CONTINUITY AND INTERACTION BETWEEN HIGHER EDUCATION CYCLES
Keywords: strategii didactice; interconexiune; cicluri ale învățământului superior; teaching strategies; continuity; interconnection; cycles of higher education